2020
DOI: 10.1186/s13006-020-00343-3
|View full text |Cite
|
Sign up to set email alerts
|

Early essential newborn care is associated with increased breastfeeding: a quasi-experimental study from Sichuan Province of Western China

Abstract: Background Breastfeeding is critical to promote maternal and child health. China has set national targets to further improve the exclusive breastfeeding rate. We aimed to examine associations between the provision of early essential newborn care (EENC) and breastfeeding outcomes among full term vaginally delivered neonates in the first 6 months of life. Methods We conducted a quasi-experimental study in eight maternal and children’s hospitals in Mianyang City and Deyang City in Sichuan Province of western Chi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…China is among the countries with the highest cesarean section rates in the world, and 40% of cesarean sections were performed without medical indication [38]. Furthermore, though the Early Essential Newborn Care (EENC) has been reported to be significantly associated with the initiation of early breastfeeding [39], the current childbirth and early newborn care policies and practices in China are not aligned with the WHO recommendations for some major interventions [40]. In addition, the medical advice to give commercial milk formula is not rare in China.…”
Section: Discussionmentioning
confidence: 99%
“…China is among the countries with the highest cesarean section rates in the world, and 40% of cesarean sections were performed without medical indication [38]. Furthermore, though the Early Essential Newborn Care (EENC) has been reported to be significantly associated with the initiation of early breastfeeding [39], the current childbirth and early newborn care policies and practices in China are not aligned with the WHO recommendations for some major interventions [40]. In addition, the medical advice to give commercial milk formula is not rare in China.…”
Section: Discussionmentioning
confidence: 99%
“…EENC was introduced to China in 2016 and had been implemented in 112 medical institutions by 2017 [ 14 ]. Yang et al surveyed the medical institutions of four provinces that implemented EENC in China and showed that only 36.2% of the newborn infants had skin-to-skin contact with their mothers, the rate of the duration of skin-to-skin contact over 90 min was 19.7%, and the breastfeeding rate and exclusive breastfeeding rate before discharge were 76.5% and 32.2%, respectively [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The core mission of this action plan is to improve the quality of newborn care services by comprehensively promoting early essential newborn care (EENC). EENC contains a package of evidence-based interventions, including simple and low-cost interventions for all infants during and immediately after birth, such as immediate and thorough drying, immediate and prolonged skin-to-skin contact between mothers and infants, and early exclusive breastfeeding [ 1 , 5 ]. The WHO pointed out that the implementation of high-quality EENC could effectively prevent prematurity, low birthweight, birth asphyxia, infection, sepsis, and other major causes of newborn morbidity and mortality [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…EENC has been introduced and implemented in over 100 medical institutions in China since 2015 [ 5 ]. Yang et al investigated the implementation of EENC in 4 provinces of China in 2019 and showed that 36.24% of mothers and newborn infants had skin-to-skin contact, among whom only 19.7% had skin-to-skin contact for more than 90 min [ 15 ].…”
Section: Introductionmentioning
confidence: 99%